Pekin ducks are motivated to lay in their preferred nest substrate. (6th March 2023) - Barrett, Lorelle; Maloney, Shane K; Blache, Dominique
Abstract: Nest design is one factor contributing to floor-laying in farmed poultry. We investigated: (i) if ducks ( Anas platyrhynchos ) prefer a particular nest substrate; and (ii) how important that preference is to them, indicated by stress-induced hyperthermia, egg albumen corticosterone, and behaviour. Twelve female ducks that were trained in a push-door task had temperature data loggers implanted. Preference testing identified the most and least preferred nest substrates between sawdust, astroturf, and hemp fibres. A behavioural demand test then required the ducks to use push-doors to access nests containing either the most or least preferred substrate. The preferred substrate door was loaded with increasing weight (0–120% of bodyweight, four nights per workload) and eventually blocked to prevent nest access. The least preferred substrate door remained unweighted. The overall rank order of substrate preferences was sawdust > hemp > astroturf. Six of the 12 birds pushed all workloads and attempted to push the blocked door. The area under the curve (AUC) of hyperthermia was larger when the preferred substrate door was blocked compared with 0%. The AUC did not differ between nights 2–4 of the blocked door compared with night 1. Egg albumen corticosterone was unaffected. We conclude that laying Pekin ducks prefer manipulatable nest substrates and accessing one is important enough to pay a cost. The results indicate that a manipulatable substrate should be provided to commercially farmed nesting ducks.